Prevalence and influencing factors of depression symptoms among grass-roots civil servants in Jiaxing city - Linghui ZHAO; Jie LING; Jingmin ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the prevalence and impact factors of depressive symptoms among grass-roots civil servants in Jiaxing city for providing evidence to conduct psychological intervention in the staff. MethodsUsing convenient sampling, an online self-administered survey was carried out among 5 780 civil servants (aged 18 - 60 years) working in government departments at district/county level and below in Jiaxing city, Zhejiang province during November - December 2021, with a self-designed questionnaire and Self-Rating Depression Scale (SDS). Multivariate logistic regression model was adopted in analyses on influencing factors of depressive symptoms among the grass-roots staff. ResultsAmong the 5 295 valid participants (91.6% of the civil servants surveyed), 1 330 (25.12%) were assessed as having depressive symptoms and the proportions of the participants having mild, moderate, and severe depression symptoms were 17.79%, 6.04%, and 1.28%, respectively. The detection rate of depressive symptoms differed significantly by gender, administrative rank of working entity, age, educational background and annual income (P < 0.05 for all). Binary multivariate logistic regression analysis showed that the middle-aged participants (31 - 40 years) had a higher risk of depressive symptoms (odds ratio [OR] = 1.303, 95% confidence interval [95%CI]:1.077 - 1.577) but the elder participants (51 - 60 years) had a lower risk (OR = 0.592, 95%CI: 0.451 - 0.777) compared to the young participants aged 18 - 30 years and that female participants had a lower risk of depressive symptoms (OR = 0.702, 95%CI: 0.609 - 0.809) in contrast to male participants. ConclusionDepressive symptoms are prevalent among grass-roots civil servants, especially among the male and middle-aged civil servants, in Jiaxing city.